PMO-178 The significance of viral and serological markers in predicting liver disease severity in e-Ag negative hepatitis b virus infection. (28th May 2012) - Audimoolam, V K; Carey, I; Bruce, M; Horner, M; Abid, S; Agarwal, K; Harrison, P
Abstract : Introduction: In hepatitis B virus (HBV) infection, seroconversion to HBeAg negative/eAb positive accompanied by low serum HBV-DNA (persistently ≤2000 IU/ml) and low quantitative HBsAg (qHBsAg) signifies transition to an inactive carrier (IC) state. However, in patients with raised serum HBV DNA differentiating those with inactive disease (ID) from eAg negative chronic HBV (eAg-CHB) currently relies on liver biopsy. This study investigated whether serological (qHBsAg) and virological markers (serum HBV DNA) can predict disease severity in patients with eAg negative HBV across a range of HBV genotypes. Methods: Liver biopsy was performed in 364 consecutive eAg negative patients (median age 38 years, 212 males) who had HBV DNA >1000 IU/ml on at least two clinic visits over 6–18 months. ALT [IU/l], qHBsAg [Abbott ARCHTECT®], HBV genotype [direct sequencing] and HBV DNA [real-time TaqMan PCR] were evaluated at the time of liver biopsy. Results: Based on the liver histology findings, 217 had ID (an Ishak fibrosis score of F0-1) and 147 had eAg-CHB (≥F2). HBV genotype-E predominated (50%) followed by D (16%), A (15%), B (10%) and C (9%). Overall qHBsAg levels were higher in ID than eAg-CHB patients (median 3.84 vs 3.7 log10 IU/ml; p=0.02). Assessment by individual genotype demonstrated that qHBsAg levels remained higher in ID than eAg-CHB in genotypes A and E (4.01 vs 3.73 and 3.95 vs 3.8 log10 IU/ml; both p<0.05). However, in genotype B qHBsAg levels correlated with the severity of fibrosis [2.81 in F0-1 vs 3.34 in F≥2; p<0.01]. The qHBsAg levels were similar in ID and eAg-CHB in genotypes C and D. HBV genotype had no impact on the severity of liver fibrosis (p=0.16). Patients with eAg-CHB compared to those with ID had raised ALT [81% vs 65 %; p<0.01], higher HBV DNA (3.99 vs 3.6 log10 IU/ml; p<0.01), older age (39 vs 36 years; p<0.01) and more were males (68% vs 51%; p<0.01). Conclusion: In eAg negative patients with HBV DNA >1000 IU/ml, the relationship between qHBsAg levels and liver fibrosis was genotype specific. Even allowing for HBV genotype, the absolute qHBsAg level was a poor discriminator of clinically significant liver fibrosis. Competing interests: V Audimoolam: None declared, I Carey Grant/Research Support from: Gilead, M Bruce: None declared, M Horner: None declared, S Abid: None declared, K Agarwal: None declared, P Harrison: None declared.